Juvenile hyperinsulinism in a Maine Coon kitten - Matthew Kornya; Anthony Abrams-Ogg; Dominique Comeau; Jeff Caswell (Journal of Feline Medicine and Surgery Open Reports, 2022)
Case summary A 5.5 month-old intact male Maine Coon cat was presented to a referral hospital for a history of muscle fasciculations, lethargy and seizures associated with refractory hypoglycemia. Diagnostic testing for hypothyroidism, hyposomatotropism or hypoadrenocorticism, inborn errors of metabolism (ie, storage diseases and urea cycle disorders), infection or iatrogenic hypoglycemia were negative. An inappropriately high serum insulin level was noted in the face of marked hypoglycemia. The insulin:glucose ratio was 0.44 (<0.3) and the amended insulin:glucose ratio was 1268 (<30). Thoracic radiography and abdominal ultrasonography did not identify a cause for this elevated insulin level. Stabilization with a low, but adequate, blood glucose occurred with corticosteroid therapy, with further significant improvement with the addition of diazoxide. Peripheral neuropathy developed several months later, and concerns for quality of life led to humane euthanasia approximately 1 year after the initial diagnosis. Insulin levels remained high at the time of euthanasia. Necropsy found no gross lesions, though microscopic degeneration of the sciatic nerve and subjectively mildly increased size and number of pancreatic islets was noted. These findings were consistent with a diagnosis of congenital hyperinsulinism. Relevance and novel information This is the first reported case of congenital hyperinsulinism in a cat and may parallel the diffuse form of hypoglycemic hyperinsulinism reported in humans and a single dog. It should be considered a differential diagnosis in kittens presenting for refractory hypoglycemia.